First line treatment with newer tyrosine kinase inhibitors in chronic myeloid leukemia associated with deep and durable molecular response – systematic review and meta-analysis. (2nd October 2016) - Gurion, Ronit; Raanani, Pia; Vidal, Liat; Leader, Avi; Gafter-Gvili, Anat
Abstract: Background: The choice of a specific tyrosine kinase inhibitor (TKI) as first line treatment in chronic myeloid leukemia (CML) is complex and influenced by multiple factors. We published a meta-analysis examining the role of newer TKIs as first line treatment in chronic phase CML. In view of the recently published data, we decided to update it. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials comparing first line treatment with imatinib to the newer TKIs (nilotinib, dasatinib, bosutinib and ponatinib). We searched MEDLINE, conference proceedings and databases of ongoing trials up to August 2015. Results: Our search yielded eight trials including 3554 patients. Treatment with the newer TKIs significantly improved major molecular response (MMR) at all time points and increased the rate of complete molecular response (CMR) at 12 and 24 months [relative risk (RR) 2.58, 95% CI 1.98–3.37, six trials and RR 2.05, 95% CI 1.63–2.58, three trials, respectively]. Early molecular response at three months was better with the newer TKIs (RR 1.33, 95% CI 1.26–1.40, six trials). Importantly, progression rate to accelerated or blastic phase was significantly lower with the newer TKIs at 12, 24 months and 5 years. Yet, there was no difference in all-cause mortality. The risk of adverse events requiring treatment discontinuation increased with the newer TKIs. Conclusions: With a longer follow-up, the newer TKIs remain more potent than imatinib, yet with no significant effect on survival. As CMR is a prerequisite for treatment discontinuation and cure, the newer TKIs favor treatment cessation.